Managing marine mollusc diseases in the context of regional and international commerce: policy issues and emerging concerns - Carnegie, Ryan; Arzul, I; Bushek, D (Philosophical Transactions of the Royal Society B: Biological Sciences, 2016)
Marine mollusc production contributes to food and economic security worldwide and provides valuable ecological services, yet diseases threaten these industries and wild populations. Although the infrastructure for mollusc aquaculture health management is well characterized, its foundations are not without flaws. Use of notifiable pathogen lists can leave blind spots with regard to detection of unlisted and emerging pathogens. Increased reliance on molecular tools has come without similar attention to diagnostic validation, raising questions about assay performance, and has been accompanied by a reduced emphasis on microscopic diagnostic expertise that could weaken pathogen detection capabilities. Persistent questions concerning pathogen biology and ecology promote regulatory paralysis that impedes trade and which could weaken biosecurity by driving commerce to surreptitious channels. Solutions that might be pursued to improve shellfish aquaculture health management include the establishment of more broad-based surveillance programmes, wider training and use of general methods like histopathology to ensure alertness to emerging diseases, an increased focus on assay assessment and validation as fundamental to assay development, investment in basic research, and application of risk analyses to improve regulation. A continual sharpening of diagnostic tools and approaches and deepening of scientific knowledge is necessary to manage diseases and promote sustainable molluscan shellfish industries.